Three potential neurovascular pathways driving the benefits of mindfulness meditation for older adults - Pommy, Jessica; Smart, Colette M.; Bryant, Andrew M.; Wang, Yang (Frontiers in Aging Neuroscience, 2023)
Mindfulness meditation has been shown to be beneficial for a range of different health conditions, impacts brain function and structure relatively quickly, and has shown promise in aging samples. Functional magnetic resonance imaging metrics provide insight into neurovascular health, which plays a key role in both normal and pathological aging processes. Experimental mindfulness meditation studies that included functional magnetic resonance metrics as an outcome measure may point to potential neurovascular mechanisms of action relevant for aging adults that have not yet been previously examined. We first review the resting-state magnetic resonance studies conducted in exclusively older adult age samples. Findings from older adult-only samples are then used to frame the findings of task magnetic resonance imaging studies conducted in both clinical and healthy adult samples. Based on the resting-state studies in older adults and the task magnetic resonance studies in adult samples, we propose three potential mechanisms by which mindfulness meditation may offer a neurovascular therapeutic benefit for older adults: 1) a direct neurovascular mechanism via increased resting-state cerebral blood flow; 2) an indirect neuroinflammatory mechanism via increased functional connectivity within the default mode network, and 3) a top-down control mechanism that likely reflects both a direct and an indirect neurovascular pathway.